Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/tpj.13531
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of inhibitors of UDP‐glucose and UDP‐sugar pyrophosphorylases for in vivo studies

Abstract: Identification and characterization of inhibitors of UDP-glucose and UDP-sugar pyrophosphorylases for in vivo studies.The Plant Journal, 90 (6) SUMMARY UDP-sugars serve as ultimate precursors in hundreds of glycosylation reactions (e.g. for protein and lipid glycosylation, synthesis of sucrose, cell wall polysaccharides, etc.), underlying an important role of UDPsugar-producing enzymes in cellular metabolism. However, genetic studies on mechanisms of UDP-sugar formation were frequently hampered by reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 68 publications
1
27
0
Order By: Relevance
“…The structure/function analyses of sugar-1-phosphates and their binding sites in the homology-derived structural models for the three pyrophosphorylases were compared with the substrate specificities that were experimentally determined for these enzymes. We also demonstrated that an inhibitor earlier shown to affect UGPase and USPase activities ( Decker et al, 2017 ), had similar effects on purified UAGPase2. The data are discussed with respect to structural determinants of substrate binding and to possible roles of each of the pyrophosphorylases in vivo.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…The structure/function analyses of sugar-1-phosphates and their binding sites in the homology-derived structural models for the three pyrophosphorylases were compared with the substrate specificities that were experimentally determined for these enzymes. We also demonstrated that an inhibitor earlier shown to affect UGPase and USPase activities ( Decker et al, 2017 ), had similar effects on purified UAGPase2. The data are discussed with respect to structural determinants of substrate binding and to possible roles of each of the pyrophosphorylases in vivo.…”
Section: Introductionsupporting
confidence: 69%
“…Barley UGPase, Arabidopsis UGPase1 and UGPase2, and Arabidopsis USPase were heterologously expressed in Escherichia coli and purified to homogeneity as earlier reported ( Martz et al, 2002 ; Meng et al, 2008 ; Decker et al, 2014 , 2017 ). An expression construct containing cDNA of Arabidopsis UAGPase2 ( At2g35020 ) was order-made by GenScript, San Francisco, CA, United States.…”
Section: Methodsmentioning
confidence: 99%
“…Sucrose and glucose often stimulate the expression of the same genes; for example, the expression of the sucrose synthase gene is induced both by glucose and sucrose (especially at higher concentrations). UDP-glucose pyrophosphorylase genes in turn are stimulated mainly by sucrose [70,71]. Recent studies have demonstrated that under reduced UDP-glucose content, the abnormal growth of vegetative and reproductive organs of plants occurred, which could be reversed by providing UDP-glucose.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the previously discussed ubiquitous expression of AtUSP and sugar-1-kinase genes (Geserick and Tenhaken, 2013b), expression profiling of Lilium and Arabidopsis glucuronokinases revealed ubiquitous expression with highest expression in pollen tubes, indicating the importance of sugar salvage or the MIOX pathway of UDP-glucuronic acid synthesis during pollen tube growth (Pieslinger et al, 2010). Notably, a class of drugs recently found to inhibit UGP and USP activity also inhibits pollen tube elongation (Decker et al, 2017). Considering the abundance of pectin-degrading activity in flowers and the wellestablished role of pectin in regulating tip growth in pollen tubes (Rhee and Somerville, 1998;Rhee et al, 2003;Palusa et al, 2007;Cao, 2012;Chebli et al, 2012), it is likely that degradation and recycling of pectin provides substrates for pollen tube growth (Geserick and Tenhaken, 2013b).…”
Section: How Important Is Wall Recycling For Reproduction?mentioning
confidence: 89%
“…Drugs have long been used as biological tools and are promising candidates for understanding the metabolic and physiological consequences of cell-wall recycling. Decker et al (2017) recently reported the characterization of a collection of chemical inhibitors of UGP and USP activity, providing a unique opportunity to monitor the metabolic flux of NDP-sugars upon perturbation of both de novo NDP-sugar biosynthesis and salvage pathways (Decker et al, 2017). In addition to pharmacological and genetic perturbation of the enzymes involved in cell-wall autodegradation and metabolic recycling, purification and genetic manipulation of plant-derived inhibitory proteins, such as PMEIs, PGIPs, and XIPs, might provide additional tools to investigate cell-wall recycling.…”
Section: New Tools For Studying Cell-wall Recyclingmentioning
confidence: 99%